2021
DOI: 10.1021/acsapm.1c00633
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Core–Shell Structure Fibers for Puerarin-Loaded Vascular Grafts

Abstract: Nowadays, small-diameter vascular grafts are attracting considerable interest in tissue engineering and are in great demand in clinical trials. However, the defect of weak patency limits the application of smallcaliber vessels in the coronary artery and peripheral vessel bypass graft surgery. Research shows that puerarin can protect endothelial cells from damage caused by inflammation, oxidative stress, and apoptosis. Simultaneously, puerarin can promote endothelial cell proliferation and differentiation. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…254 They can be added to different materials to overcome their mechanical limitations. 255 Moreover, by incorporating different types of carbon nanostructures in brous systems, their mechanical properties can be altered as desired for specic tissue engineering applications. 256,257 3.4.…”
Section: Fibrous Carbon Nanostructuresmentioning
confidence: 99%
“…254 They can be added to different materials to overcome their mechanical limitations. 255 Moreover, by incorporating different types of carbon nanostructures in brous systems, their mechanical properties can be altered as desired for specic tissue engineering applications. 256,257 3.4.…”
Section: Fibrous Carbon Nanostructuresmentioning
confidence: 99%
“…The distance was maintained at 14 cm and feeding rate was kept in 1 mL/h. In order to investigate the influences on fiber morphology, different voltages (10,16, and 20 kV) were applied. The spinning time was 4 h and the temperature was kept at 45 C. After electrospinning, the fibrous membranes were placed in a vacuum drying oven at 50 C for 24 h to remove the residual solvent.…”
Section: Electrospinning Processmentioning
confidence: 99%
“…Electrospinning, which has received great attention in the past decades, is unique and effective method of producing nanofibers from various polymers for a wide range of application, especially in the pharmaceutical and medical fields, involving drug delivery, [1][2][3][4][5] tissue engineering scaffolds, [6][7][8][9][10] and wound dressing. [11][12][13][14][15][16][17][18][19][20] In the electrospinning process, solutions of polymers are applied to an electric field force opposite to the direction of surface tension under the action of high voltage.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, functional molecules such as growth factors or active substances could be loaded inside the fibers, allowing the active substances in the material to have a better regulatory effect through continuous and slow release. Han et al ( Han et al, 2021 ) prepared a functional graft loading with puerarin to promote endothelial cell proliferation and differentiation, in which the puerarin with an antiplatelet aggregation effect was used as core layer of the fibers, and Gel/PLLA was used as fiber shell layer. The results showed that puerarin could achieve long-term efficient release, the material had good mechanical properties and degradability, and the biocompatibility results indicated that the core–shell fiber prepared in this way had no cytotoxicity to endothelial cells and did not cause hemolysis.…”
Section: Introductionmentioning
confidence: 99%